Modified conductive material and application thereof

By modifying alkyl diamine compounds with PEDOT:PSS composite chain extension, a modified conductive material was prepared, which solved the problem of low conductivity of LMFP positive electrode materials, significantly improved electron conduction and ion diffusion rates, and improved the electrochemical performance of lithium-ion batteries.

CN119517487APending Publication Date: 2025-02-25EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411240052.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The low ionic conductivity and electronic conductivity of the existing lithium manganese iron phosphate (LMFP) cathode material seriously restricts its promotion and application in lithium-ion batteries.

Method used

By combining alkyldiamine compounds with poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS), a modified conductive material was prepared, which enhances the molecular arrangement order and conductivity of the conductive material, thereby improving the electron conduction and ion diffusion rate of the positive electrode material.

Benefits of technology

The modified conductive material significantly improves the electron conduction and ion diffusion rate of the positive electrode material, reduces internal resistance, and improves the electrochemical performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a modified conductive material and application thereof, the modified conductive material comprises a first conductive agent, and the first conductive agent is obtained by performing composite chain extension modification on poly (3, 4-ethylenedioxythiophene)-poly (styrene sulfonic acid) (PEDOT: PSS) by an alkyl diamine compound. According to the first conductive agent provided by the invention, by utilizing two active functional groups (-NH2) of the alkyl diamine compound, the alkyl diamine compound can react with a plurality of sulfonic acid groups of PEDOT: PSS, so that the interaction between the PEDOT and the PSS is enhanced, the molecular arrangement of the first conductive agent is more ordered, and higher conductivity is shown; therefore, the electron conduction and ion diffusion rate of the positive electrode material can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, and in particular relates to a modified conductive material and application thereof. Background Art

[0002] As the new energy vehicle market gradually expands and the application scenarios become more and more extensive, phosphate system cathode materials are widely used in the fields of power batteries and energy storage batteries because of their low cost and good safety performance. At present, the energy density of lithium iron phosphate, the mainstream cathode material on the market, has almost reached its upper limit. Therefore, lithium manganese iron phosphate (LMFP) cathode materials with the same olivine structure as lithium iron phosphate have been gradually developed. They not only retain the same safety performance as lithium iron phosphate, but also have better thermal stability, chemical stability and economy than ternary materials, and at the same time have higher energy density than lithium iron phosphate. However, LMFP exhibits low ionic conductivity and electronic conductivity, which seriously restricts the promotion and application of this cathode material.

[0003] As the core of lithium-ion batteries, the main positive electrode material affects many electrochemical properties of the battery, such as charge and discharge capacity, cycle life, platform voltage, rate performance, internal resistance, etc. Therefore, the development of positive electrode materials has always been the core of battery cell development. The low conductivity of the main positive electrode material will lead to insufficient electron conduction and lithium ion diffusion rate, increased internal resistance, and thus cause many electrochemical performance disadvantages of lithium-ion batteries. In order to improve this defect, a certain conductive agent is usually added to improve the conductivity of the positive electrode material, optimize the conductive network of the battery cell, promote electron conduction and lithium ion diffusion rate, reduce internal resistance, and thus improve the electrochemical performance of lithium-ion batteries. However, in the prior art, relevant technicians have found that by introducing conventional conductive agents into the main positive electrode material, such as carbon nanotubes, carbon black, vapor-grown carbon fiber reinforcement and other conductors, the promotion of the electron conduction and ion diffusion rate of the main positive electrode material is not obvious. Summary of the invention

[0004] In order to improve the electron conduction and ion diffusion rate of the positive electrode material, the present invention provides a modified conductive material and application thereof.

[0005] According to a first aspect of the present invention, a modified conductive material is provided, the modified conductive material comprising a first conductive agent, the first conductive agent being obtained by performing a composite chain extension modification on poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS) by an alkyl diamine compound. The first conductive agent provided by the present invention can react with multiple sulfonic acid groups of PEDOT:PSS by utilizing two active functional groups (-NH2) possessed by the alkyl diamine compound, thereby enhancing the interaction between PEDOT and PSS, making the molecular arrangement of the first conductive agent more orderly, exhibiting a higher conductivity, and thus effectively improving the electronic conduction and ion diffusion rate of the positive electrode material.

[0006] Preferably, the alkyldiamine compound includes at least one of 1,4-butanediamine hydrochloride (BA), 1,6-hexanediamine hydrochloride (HA) and 1,8-octanediamine (OA).

[0007] Preferably, calculated by mass ratio, poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid):alkyl diamine compound=(8000-10000):(20-30).

[0008] Preferably, the method for preparing the first conductive agent comprises the following steps: preparing PEDOT:PSS into an aqueous solution, adding an alkyl diamine compound, and reacting at room temperature for 12 to 14 hours to obtain the first conductive agent. The modification method provided by the present invention is a simple and effective method.

[0009] Preferably, the concentration of PEDOT:PSS is 8-12 mg / mL.

[0010] Preferably, the concentration of the alkyl diamine compound is 0.5-2 mg / mL.

[0011] Preferably, the modified conductive material further includes a second conductive agent, and the second conductive agent includes graphene oxide (rGO), carbon nanotubes (CNTs), and carbon black (SP).

[0012] Preferably, the method for preparing the second conductive agent comprises the following steps: S1. separately preparing a first suspension comprising graphene and a second suspension comprising carbon nanotubes and carbon black, mixing the first suspension with the second suspension, and then dispersing them at room temperature for 2 to 3 hours to obtain a mixed solution; S2. then freeze-drying the mixed solution to obtain a composite material, placing it in an inert gas atmosphere at 400 to 600°C for reaction for 4 to 6 hours to obtain a second conductive agent.

[0013] The second conductive agent provided by the present invention is rGO / CNTs / SP aerogel, which is a three-dimensional porous solid material formed by the mutual aggregation of nanoparticles or polymer molecules, and has the advantages of low density, high porosity, large specific surface area, low thermal conductivity, etc. When the first conductive agent is compounded with the second conductive agent, the electron conduction and ion diffusion rate of the positive electrode material can be further improved.

[0014] Preferably, calculated by mass ratio, graphene oxide: carbon nanotube: carbon black = 4-5: 4-5: 2-3.

[0015] Preferably, calculated by volume ratio, the first suspension: the second suspension = 4-5:3-4.

[0016] Preferably, the concentration of graphene oxide in the first suspension is 0.005-0.007 g / mL.

[0017] Preferably, the concentration of the carbon nanotubes in the second suspension is 0.01-0.015 g / mL.

[0018] Preferably, the concentration of carbon black in the second suspension is 0.005 to 0.0075 g / mL.

[0019] Preferably, in the modified conductive material, calculated by mass ratio, the first conductive agent: the second conductive agent = 1-2: 1-3.

[0020] Preferably, the method for preparing the modified conductive material comprises the following steps: mixing the first conductive agent and the second conductive agent, then adding an organic solvent, and subjecting the mixture to ultrasonic treatment and vacuum drying to obtain the modified conductive material.

[0021] Preferably, the vacuum drying treatment is vacuum drying at 50-70° C. for 5-7 hours. According to a second aspect of the present invention, a positive electrode material is provided, the positive electrode material comprising the modified conductive material as described above.

[0022] Preferably, the positive electrode material further comprises a positive electrode active material, and the positive electrode active material comprises at least one of lithium iron manganese phosphate and lithium iron phosphate material, wherein the chemical formula of lithium iron manganese phosphate is LiMn a Fe (1-a) PO4, 0.5 <a<0.7。

[0023] According to a third aspect of the present invention, there is provided a positive electrode, which comprises the positive electrode material as described above.

[0024] According to a fourth aspect of the present invention, there is provided a battery comprising the positive electrode as described above. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0026] Example 1

[0027] (1) Preparation of the first conductive agent

[0028] The preparation of the first conductive agent includes the following steps: directly adding 25 mL of 1 mg / mL solid additive 1,6-hexanediamine hydrochloride (HA) to 900 mL of 10 mg / mL poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS, CAS No. 155090-83-8) aqueous solution, and stirring at room temperature for 12 hours to obtain a modified first conductive agent (PEDOT:PSS-HA).

[0029] (2) Preparation of the Second Conductive Agent

[0030] The preparation of the second conductive agent comprises the following steps:

[0031] S1. 4.5 g of GO was added to 800 mL of deionized water to obtain a first suspension, 4.5 g of CNTs and 2.5 g of SP were added to 400 mL of deionized water to obtain a second suspension, and the first suspension and the second suspension were treated in an ultrasonic bath for 5 hours respectively, and then 80 mL of the first suspension was mixed with 60 mL of the second suspension, stirred at room temperature for 2 hours, and ultrasonically dispersed for 1 hour to obtain a mixed solution;

[0032] S2. Pour the mixed liquid into a polytetrafluoroethylene mold, quickly freeze them with liquid nitrogen, and then quickly put them into a pre-cooled vacuum freeze dryer for 48 hours. After obtaining the composite material, place it in a nitrogen environment and treat it at 500°C for 5 hours to obtain a second conductive agent.

[0033] (3) Preparation of modified conductive materials

[0034] The preparation of the modified conductive material includes the following steps: mixing the first conductive agent and the second conductive agent in a mass ratio of 1:1, then adding 900 μL (5 vol%) dimethyl sulfoxide (DMSO), treating in an ultrasonic bath for 2.5 hours, and vacuum drying at 60° C. for 6 hours to obtain a modified conductive material.

[0035] (4) Application of modified conductive materials

[0036] The positive electrode slurry was prepared by stirring LMFP: modified conductive material: PVDF: polyvinyl pyrrolidone (PVP) in a mass ratio of 97.2:0.9:1.7:0.2, and the negative electrode slurry was prepared by stirring graphite: SP: CMC: SBR in a mass ratio of 96.7:0.6:1.2:1.5. The prepared positive and negative electrode slurries were respectively coated on both sides of the current collector, passed through an oven, roller pressed, and then rolled up; the positive and negative electrodes were cut into pole pieces of a certain size, and stacked into a core package by a negative electrode-diaphragm-positive electrode stacking method, and finally the core package was put into a shell and assembled into a battery.

[0037] Example 2

[0038] This example prepares a modified conductive material, a positive electrode material, a positive electrode, and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the modified conductive material, this example uses 1,4-butanediamine hydrochloride (BA) instead of 1,6-hexanediamine hydrochloride (HA) in equal parts by mass. Except for the above differences, the operating steps for preparing the modified conductive material in this example are strictly consistent with those in Example 1.

[0039] Example 3

[0040] This example prepares a modified conductive material, a positive electrode material, a positive electrode, and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the modified conductive material, this example uses an equal mass fraction of 1,8-octanediamine (OA) to replace 1,6-hexanediamine hydrochloride (HA). Except for the above difference, the operating steps for preparing the modified conductive material in this example are strictly consistent with those in Example 1.

[0041] Example 4

[0042] This example prepares modified conductive materials, positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the modified conductive material, this example uses a mass ratio of first conductive agent: second conductive agent = 2:1 (the total mass fractions of the first conductive agent and the second conductive agent remain unchanged). Except for the above differences, the operating steps for preparing the modified conductive material in this example are strictly consistent with those in Example 1.

[0043] Example 5

[0044] This example prepares modified conductive materials, positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the modified conductive materials in this example, the mass ratio of the first conductive agent: the second conductive agent is calculated to be 1:3 (the total mass fractions of the first conductive agent and the second conductive agent remain unchanged). Except for the above differences, the operating steps for preparing the modified conductive materials in this example are strictly consistent with those in Example 1.

[0045] Example 6

[0046] This example prepares modified conductive materials, positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the modified conductive material, this example uses a mass ratio of the first conductive agent: the second conductive agent = 1:4 (the total mass fractions of the first conductive agent and the second conductive agent remain unchanged). Except for the above differences, the operating steps for preparing the modified conductive material in this example are strictly consistent with those in Example 1.

[0047] Example 7

[0048] This example prepares a modified conductive material, a positive electrode material, a positive electrode, and a lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the modified conductive material in this example, the mass ratio of PEDOT:PSS:HA is calculated as 8000:20 (800mL of 10mg / mL PEDOT:PSS, 20mL of 1mg / mL HA). Except for the above difference, the operating steps for preparing the modified conductive material in this example are strictly consistent with those in Example 1.

[0049] Example 8

[0050] This example prepares a modified conductive material, a positive electrode material, a positive electrode, and a lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the modified conductive material, this example uses a mass ratio of PEDOT:PSS:HA=10000:30 (1000mL of 10mg / mL PEDOT:PSS, 30mL of 1mg / mL HA). Except for the above differences, the operating steps for preparing the modified conductive material in this example are strictly consistent with those in Example 1.

[0051] Example 9

[0052] This example prepares a modified conductive material, a positive electrode material, a positive electrode, and a lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the modified conductive material in this example, the mass ratio of PEDOT:PSS:HA is calculated as 6000:30 (600mL of 40mg / mL PEDOT:PSS, 30mL of 1mg / mL HA). Except for the above differences, the operating steps for preparing the modified conductive material in this example are strictly consistent with those in Example 1.

[0053] Example 10

[0054] This embodiment prepares a modified conductive material, a positive electrode material, a positive electrode, and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the modified conductive material, this embodiment uses other methods to prepare the second conductive agent. Except for the above differences, the operation steps for preparing the modified conductive material in this embodiment are strictly consistent with those in Example 1. Specifically, the method for preparing the second conductive agent is: by ball milling, graphene oxide, carbon nanotubes, and carbon black are uniformly mixed, and treated at 500° C. for 4 to 5 hours to obtain the second conductive agent.

[0055] Embodiment 11

[0056] This embodiment prepares positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Embodiment 1. The difference from Embodiment 1 is that when preparing the positive electrode materials, this embodiment uses an equal mass fraction of the first conductive agent to replace the modified conductive material. Except for the above differences, the operating steps for preparing the modified conductive material in this embodiment are strictly consistent with those in Embodiment 1.

[0057] Example 12

[0058] This embodiment prepares positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Embodiment 1. The difference from Embodiment 1 is that when preparing the positive electrode materials, this embodiment uses lithium iron phosphate (LFP) in equal parts by mass to replace lithium manganese iron phosphate materials (LMFP). Except for the above differences, the operating steps for preparing the modified conductive material in this embodiment are strictly consistent with those in Embodiment 1.

[0059] Example 13

[0060] This embodiment refers to the formula and method provided in Example 1 to prepare positive electrode materials, positive electrodes, and lithium-ion batteries. The difference from Example 1 is that when preparing positive electrode materials, this embodiment uses ternary materials (LiNi 0.8 Co 0.1 Mn 0.1 O2) replaces lithium manganese iron phosphate material (LMFP). Except for the above differences, the operation steps for preparing the modified conductive material in this embodiment are strictly consistent with those in Example 1.

[0061] Comparative Example 1

[0062] This comparative example prepares positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the positive electrode materials, this comparative example uses an equal mass fraction of CNTs to replace the modified conductive material. Except for the above differences, the operating steps for preparing the modified conductive material in this comparative example are strictly consistent with those in Example 1.

[0063] Comparative Example 2

[0064] This comparative example prepares positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the positive electrode materials, this comparative example uses an equal mass fraction of SP to replace the modified conductive material. Except for the above differences, the operating steps for preparing the modified conductive material in this comparative example are strictly consistent with those in Example 1.

[0065] Comparative Example 3

[0066] This comparative example prepares positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that, when preparing the positive electrode materials, this comparative example uses rGO in equal mass fractions to replace the modified conductive material. Except for the above differences, the operating steps for preparing the modified conductive material in this comparative example are strictly consistent with those in Example 1.

[0067] Comparative Example 4

[0068] This comparative example prepares positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the positive electrode materials, this comparative example uses a conventional conductive agent mixture of equal mass parts (rGO: CNTs: SP = 4.5:4.5:2.5) to replace the modified conductive material. Except for the above differences, the operating steps for preparing the modified conductive material in this comparative example are strictly consistent with those in Example 1.

[0069] Comparative Example 5

[0070] This comparative example prepares positive electrode materials, positive electrodes, and lithium-ion batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the positive electrode material, the modified conductive material is replaced by an equal mass fraction of a second conductive agent. Except for the above differences, the operating steps for preparing the modified conductive material in this comparative example are strictly consistent with those in Example 1.

[0071] Test Case

[0072] 1. Test subjects

[0073] The modified conductive materials prepared in Examples 1 to 11 and Comparative Examples 1 to 5 and the batteries using the modified conductive materials.

[0074] 2. Test Method

[0075] (1) Conductivity: The conductivity test adopts the four-probe method, which uses four metal probes arranged at equal intervals to contact the sample surface. By measuring the voltage and current between the probes, the resistance value of the sample is obtained, and finally the conductivity is obtained.

[0076] (2) Capacity retention rate: The capacity retention rate of the battery was tested according to the following method steps, wherein the capacity retention rate was calculated by formula (I).

[0077] Capacity retention rate = C x / C0×100% formula (I)

[0078] ① Capacity test before cycling: At an ambient temperature of 25±2℃, discharge the battery at a constant current of 0.33C to 2.5V, and leave it for 10 minutes. Then charge the battery at a constant current of 0.33C to 4.2V, and then switch to constant voltage charging at 4.2V until the charging current is less than or equal to 0.05C. Leave it for 30 minutes. Discharge the battery at a constant current of 0.3C until the voltage reaches 2.5V, leave it for 30 minutes, and record the discharge capacity C0

[0079] ② Cycle test: Test the battery at an ambient temperature of 25±2℃; a. Charge the battery at a constant current of 1C to 4.2V and then switch to constant voltage charging to 0.05C and cut off; b. Leave for 30 minutes; c. Discharge at a current of 1C to 2.5V; d. Leave for 30 minutes and repeat steps a to d for 500 cycles.

[0080] ③ Post-cycle capacity test: At an ambient temperature of 25±2℃, discharge the battery at a current of 0.33C to 2.5V and leave it for 10min. Then charge the battery at a constant current of 0.33C to 4.2V, then switch to constant voltage charging at 4.2V until the charging current is less than or equal to 0.05C and leave it for 30min. The battery is discharged at a current of 0.3C until the voltage reaches 2.5V, leave it for 30min, and record the discharge capacity C x .

[0081] 3. Result testing and analysis

[0082] The experimental data of this test example are shown in Table 1. Among them, it can be confirmed through Examples 1 to 3 that the two active functional groups (-NH2) of the alkyl diamine compound can interact with multiple sulfonic acid groups of PEDOT:PSS, thereby enhancing the interaction between PEDOT and PSS, thereby effectively improving the electronic conduction and ion diffusion rate of the positive electrode material. Combined with Example 11, it can be seen that when PEDOT:PSS-HA is composited with rGO / CNTs / SP aerogel to form a modified conductive material, the electronic conduction and ion diffusion rate of the positive electrode material can be further improved.

[0083] It can be seen from Examples 1 and 4 to 6 that in the modified conductive material, when the mass ratio of the first conductive agent to the second conductive agent satisfies the range of 1 to 2:1 to 1.5, the conductive performance of the modified conductive material in LMFP can be further enhanced, thereby enhancing the cycle performance of the battery using it.

[0084] Combining Example 1 and Examples 7 to 9, it can be seen that when preparing the first conductive agent, the mass ratio of PEDOT:PSS to the alkyl diamine compound will affect the conductivity of the first conductive agent in the modified conductive material, thereby affecting the cycle performance of the battery using it. When the mass ratio of PEDOT:PSS to the alkyl diamine compound satisfies 8000 to 10000:20 to 30 when preparing the first conductive agent, the first conductive agent has better performance.

[0085] In Example 1 and Example 10, it can be proved that the preparation method of the second conductive agent, rGO has strong hydrophilicity and can be evenly dispersed in an aqueous solution, so the corresponding aerogel can be obtained through the rGO aqueous solution. However, similarly, it is precisely because of the strong hydrophilicity of rGO that the conductivity of the second conductive agent prepared by other methods decreases.

[0086] It can be seen from Examples 1 and 12 to 13 that the modified conductive material provided by the present invention is applicable to most of the positive electrode materials currently on the market, such as LMFP, LFP and ternary materials. However, its promoting effect on LMFP and LFP materials is better than that on other positive electrode materials.

[0087] As can be seen from Comparative Examples 1 to 4, compared with the modified conductive material provided by the present invention, the introduction of conventional conductive agents, such as carbon nanotubes, carbon black, vapor-grown carbon fiber reinforcements and other conductive agents, into the positive electrode main material does not significantly promote the electron conduction and ion diffusion rate of the positive electrode main material. Moreover, it can also be seen from Comparative Example 5 that only adding the second conductive agent to the positive electrode main material to prepare the positive electrode material, its cycle efficiency is also difficult to achieve the effect of the first conductive agent and the second conductive agent after the composite.

[0088] Table 1. Test results of this test case

[0089] Group <![CDATA[Conductivity (S·cm -1 )]]> Capacity retention rate / % Example 1 1788 96.9 Example 2 1515 95.8 Example 3 1340 95.5 Example 4 1289 95.2 Example 5 1178 95.0 Example 6 894 94.5 Example 7 1350 95.6 Example 8 1250 95.1 Example 9 794 94.2 Example 10 894 93.5 Embodiment 11 278 92.0 Example 12 2150 97.8 Example 13 2645 96.4 Comparative Example 1 554 92.8 Comparative Example 2 325 92.4 Comparative Example 3 105 91.7 Comparative Example 4 540 92.8 Comparative Example 5 899 94.0

[0090] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A modified conductive material, characterized in that: The modified conductive material includes a first conductive agent, which is obtained by modifying poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) with an alkyl diamine compound.

2. The modified conductive material according to claim 1, characterized in that: The alkyl diamine compound includes at least one of 1,4-butanediamine hydrochloride, 1,6-hexanediamine hydrochloride and 1,8-octanediamine.

3. The modified conductive material according to claim 1 or 2, characterized in that: Calculated by mass ratio, the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid):the alkyl diamine compound=(8000-10000):(20-30).

4. The modified conductive material according to claim 1, characterized in that: The modified conductive material also includes a second conductive agent, which includes graphene oxide, carbon nanotubes, and carbon black.

5. The modified conductive material according to claim 4, characterized in that: The method for preparing the second conductive agent comprises the following steps: S1. preparing a first suspension comprising the graphene oxide and a second suspension comprising the carbon nanotubes and the carbon black, respectively, mixing the first suspension with the second suspension, and then dispersing at room temperature to obtain a mixed solution; S2. The mixed solution is then freeze-dried to obtain a composite material, which is then placed in an inert gas atmosphere for reaction at 400-600° C. for 4-6 hours to obtain the second conductive agent.

6. The modified conductive material according to claim 4, characterized in that: Calculated by mass ratio, the graphene oxide: the carbon nanotube: the carbon black = 4-5: 4-5: 2-3.

7. The modified conductive material according to claim 4, characterized in that: In the modified conductive material, calculated by mass ratio, the first conductive agent: the second conductive agent = 1-2: 1-3.

8. A positive electrode material, characterized in that The positive electrode material includes the modified conductive material according to any one of claims 1 to 7.

9. A positive electrode, characterized in that The positive electrode comprises the positive electrode material as claimed in claim 8.

10. A battery, characterized in that: The battery comprises the positive electrode as claimed in claim 9.